2006
DOI: 10.1021/jf052021o
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Carbofuran and Diuron Pesticides in 43 Tropical Soils of Sri Lanka

Abstract: To better understand the environmental fate of pesticides in Sri Lankan soils, we studied the sorption behavior of two commonly used pesticides (carbofuran and diuron) in 43 surface soils representing a range of soil physicochemical properties from dry and wet zones of Sri Lanka. For carbofuran, the K(d) (L/kg) values varied from 0.11 to 4.1 (mean, 0.83; median, 0.62) and K(oc) ranged from 7.3 to 120.6 (mean, 41.65; median, 36.1), whereas for diuron K(d) values varied from 0.5 to 75 (mean, 9.6; median, 5.15) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 17 publications
8
25
1
2
Order By: Relevance
“…Figure 2 shows that K d across all samples was strongly correlated with the soil C content (r 2 = 0.71, significance level 0.001). The relationship between K d for diuron and C content is consistent with the findings of others [14,18]. Sorption coefficients normalized for organic C content (K OC ) were calculated and these are also presented in Table 1.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Figure 2 shows that K d across all samples was strongly correlated with the soil C content (r 2 = 0.71, significance level 0.001). The relationship between K d for diuron and C content is consistent with the findings of others [14,18]. Sorption coefficients normalized for organic C content (K OC ) were calculated and these are also presented in Table 1.…”
Section: Resultssupporting
confidence: 87%
“…Sorption coefficients normalized for organic C content (K OC ) were calculated and these are also presented in Table 1. The average K OC value across all of the soils was 723 Lkg -1 , which is higher than the average diuron K OC values reported in previous studies [13,14,18,20,22]. However, the average for the A11 horizons of 487 Lkg -1 is quite consistent with these literature values and represents a more meaningful comparison given that most literature values are for topsoils.…”
Section: Resultssupporting
confidence: 76%
“…Results of the current study showed that K d and K oc values strongly correlated with soil organic carbon. This result was in agreement with Hance (25), Grover (26), Liyanage et al (27), Wang and Keller (28) and Umali et al (6) findings, which reported consistent relationships between K d for diuron and carbon content. Wang and Keller (28) assessed diuron and atrazine sorption to soil particles in different sizes for four soils and one sediment in Santa Barbara, California, The USA.…”
Section: Discussionsupporting
confidence: 92%
“…(Yen et al, 1997) The data in Table 17 suggest that low sorption values are the result of inadequate testing. However, for another 43 tropical soils, Kd and Koc (L.kg -1 ) values for carbofuran determined with a batch method (only one concentration tested) were reported (Liyanage et al, 2006). The soil-water ratio was 5:10.…”
Section: Ept With Parathionmentioning
confidence: 95%